2018
DOI: 10.1111/ijpp.12462
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacist-led interventions and their impact on patients’ medication adherence and other health outcomes: a systematic review

Abstract: Community pharmacist-led interventions have been shown to contribute to improved adherence and better disease control. Future research should attempt to better understand which particular intervention components make the greatest contribution towards improving adherence and health outcomes, for patients with different medical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
149
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(158 citation statements)
references
References 51 publications
5
149
0
4
Order By: Relevance
“…In fact, pharmacists, as the most easily accessible members of the treatment team, can inform patients and their families of the outcomes of pharmacotherapy, thereby convincing them to pursue their prescriptions. For example, a recent study systematically reviewed pharmacists‐led contributions to increasing patients' adherence to pharmacotherapy …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, pharmacists, as the most easily accessible members of the treatment team, can inform patients and their families of the outcomes of pharmacotherapy, thereby convincing them to pursue their prescriptions. For example, a recent study systematically reviewed pharmacists‐led contributions to increasing patients' adherence to pharmacotherapy …”
Section: Discussionsupporting
confidence: 93%
“…This highlights the paramount role of both pharmacists and physicians in helping patients better adapt themselves to the treatment by informing them of the side effects of drugs and strategies to deal with them. For instance, researchers have empirically manifested the strategic role of pharmacists and physicians in increasing patients' adherence to medications . More specifically, a recent study conducted on physicians who were specialized in treating patients with psychiatric disorders showed if prescribers were provided with information on non‐adherence, they would effectively manage pharmacotherapy …”
Section: Discussionmentioning
confidence: 99%
“…[23] Some other studies also corroborate these findings, such as the metaanalysis conducted by Milosavljevic, in which, of a total of 65 articles reviewed, 22 studies show a 61.5% improvement in adherence, in favor of the educational intervention group (counseling person -person, with detailed knowledge about disease prevention and management) compared to the control group (regular advice provided with the medical prescription), with significant results (p<0.05). [24] Previous systematic reviews have shown that the highest percentage of adherence failure reduction linked to an educational intervention strategy is 45.5% and the lowest is 4,8%. In the following Table 4 a comparison is made between the studies carried out on the measurement of adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists are accessible health care professionals with extensive medication and disease state training. Pharmacists routinely engage with patients in a variety of settings which provides opportunities to identify and counsel patients with poor medication adherence 18 . Evidence suggests pharmacist‐led interventions can have a positive impact on medication adherence, chronic disease management, and patient outcomes 18,19 .…”
mentioning
confidence: 99%
“…Pharmacists routinely engage with patients in a variety of settings which provides opportunities to identify and counsel patients with poor medication adherence 18 . Evidence suggests pharmacist‐led interventions can have a positive impact on medication adherence, chronic disease management, and patient outcomes 18,19 . A comprehensive systematic review with focused meta‐analyses found significant results in favor of pharmacists' direct patient care interventions and services in medication adherence ( P = .001).…”
mentioning
confidence: 99%